European labour law - Blanpain, R. (Roger), 1932- (Kluwer Law International, 2002)
This book deals with European labour law and industrial relations. It covers legislation concerning relations between employers and employees, collective agreements and the case law of the Court of Justice, as well as the structure and strategies of the social actors.